ANALISIS RISIKO BAHAYA KECELAKAAN KERJA DENGAN IDENTIFIKASI DAN ANALISIS RISIKO KECELAKAAN KERJA DENGAN METODE JSA (JOB SAFETY ANALYSIS) PADA PT SINAR SEMESTA - Mubarak S, Akhmad; Nugroho, Andung Jati (Yayasan Education and Social Center, 2025)
PT Sinar Semesta is a company engaged in the casting and machining industry. During production processes, workers are exposed to hazardous materials and face potential risks such as workplace accidents, fires, and environmental pollution. To identify and mitigate these risks, the company implements the Job Safety Analysis (JSA) method. This approach is used to analyze various workplace hazards and establish preventive measures to minimize accidents. Based on the analysis, 13 types of jobs were identified as high-risk, particularly in the induction, casting, and molding stages. Some of these jobs fall into the very high-risk category, posing serious accident threats. Therefore, implementing JSA is an effective strategy for reducing workplace hazards. To enhance occupational safety, the company must prioritize control measures, provide adequate safety facilities, and ensure that workers properly utilize Personal Protective Equipment (PPE). These steps are crucial in creating a safer and more secure work environment.